Improvement of Human Body Model Rib Fracture Risk Prediction: Creation of injury risk curves and rib cortical bone regression models for age adjusted risk prediction - Blennow, Amanda (My University, 2020)
In motor vehicle collision, one of the most commonly injured body regions is the thorax and these injuries are in many cases the cause of death among belted, adult drivers. Rib fractures are particularly dangerous among elderly and to enable injury prevention, proper risk assessment is of great importance. In a recent study, the effect of age, sex and strain rate on the rib cortical bone material was investigated, enabling creation of new injury risk curves and rib cortical bone material models.The aim of this thesis was thus to improve the human body model rib fracture risk prediction by creating new rib fracture risk curves and material models of human rib cortical bone for individually adapted rib fracture risk prediction. Using the methods of parametric survival modelling, injury risk curves for rib fracture risk prediction were developed for prediction using both ultimate strain and total strain energy density. It was found that the new strain based risk curve corresponds to a decrease in ultimate strain of 12 % per decade of life, compared to the 5 % per decade of life in the currently used risk curve. Regression models of the mechanical properties elastic modulus, plastic hardening modulus and yield stress, of human rib cortical bone were created and thus, construction of age dependent stress-strain curves was enabled. The stress-strain curves also model the individual variability, suggesting mechanical parameter values for weak, average and strong individuals of any given age. The material models were implemented in the SAFER HBM and four post mortem human subject sled tests were reproduced and outputs were evaluated with both the newly created injury risk curves and the injury risk curves that have been used up until now. It was found that both the new injury risk curves and the material models affected the predicted injury risks and particularly among elderly. Due to the large set of data used for the development of injury risk curves, the new strain-based risk curve possesses a higher statistical validity, compared to the old strain-based risk curve, and can therefore be considered as a better alternative. The energy-based risk prediction proved to be less sensitive to the material model used compared to the strain-based risk prediction . This is promising in terms of predicting risks that are less sensitive to individual variability.
Keywords: Injury Risk Curve; Rib Fracture Risk; Risk Prediction; Regression; Rib Cortical Bone; Material Model; Survival Analysis; Human Body Model